Composite substrate, method for manufacturing composite substrate, and method for manufacturing gallium oxide crystal film

CN116888310BActive Publication Date: 2026-10-30NGK INSULATORS LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202280016510.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-04-27
Filing Date
2022-02-28
Publication Date
2026-10-30
Estimated Expiration
2042-02-28

AI Technical Summary

Benefits of technology

[0011]在本发明的复合基板及复合基板的制法中,能够提供抑制了α-Ga2O3晶体膜与基底基板之间的剥离的复合基板。得到这样的效果的理由被推测是因为,例如,碱金属元素的至少1种以适合的浓度包含于α-Ga2O3晶体膜中。本发明的复合基板的制法适用于制造抑制了α-Ga2O3晶体膜与基底基板之间的剥离的复合基板。而且,在本发明的氧化镓晶体膜的制法中,从抑制了α-Ga2O3晶体膜与基底基板之间的剥离的裂纹少的复合基板除去基底基板而得到自支撑的α-Ga2O3晶体膜,因此能得到裂纹少的氧化镓晶体膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116888310B_ABST
    Figure CN116888310B_ABST
Patent Text Reader

Abstract

The composite substrate (50) has a base substrate (52) and an α-Ga2O3 crystal film (54) provided on the base substrate (52). The α-Ga2O3 crystal film (54) has a film thickness of 10 μm or more, and a content of at least one of alkali metal elements is 1.2 x 10 15 atoms / cm 3 or less. 18 atoms / cm 3 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to composite substrates, methods for manufacturing composite substrates, and methods for manufacturing gallium oxide crystal films. Background Technology

[0002] In recent years, gallium oxide (Ga2O3) has attracted attention as a semiconductor material. Gallium oxide is known to have five crystal forms: α, β, γ, δ, and ε. Among them, α-Ga2O3, as a metastable phase, has a very large band gap of 5.3 eV, making it highly anticipated as a power semiconductor material. For example, Patent Document 1 discloses a semiconductor device comprising a substrate having a corundum-type crystal structure, a semiconductor layer having a corundum-type crystal structure, and an insulating film having a corundum-type crystal structure, and describes an example of forming an α-Ga2O3 film on a sapphire substrate as the semiconductor layer. Furthermore, Patent Document 2 discloses a semiconductor device comprising: an n-type semiconductor layer mainly composed of a crystalline oxide semiconductor with a corundum structure; a p-type semiconductor layer mainly composed of an inorganic compound with a hexagonal crystal structure; and electrodes. In an embodiment of Patent Document 2, a diode is fabricated by forming an α-Ga₂O₃ film with a corundum structure as a metastable phase, which serves as an n-type semiconductor layer, and an α-Rh₂O₃ film with a hexagonal crystal structure, as a p-type semiconductor layer on a c-plane sapphire substrate. Furthermore, α-Ga₂O₃ is also expected to be used in phosphors. Existing technical documents Patent documents

[0003] Patent Document 1: Japanese Patent Application Publication No. 2014-72533 Patent Document 2: Japanese Patent Application Publication No. 2016-25256 Summary of the Invention The problem that the invention aims to solve

[0004] However, to achieve a thick α-Ga₂O₃ crystal film, delamination occurs between the α-Ga₂O₃ crystal film and the substrate during growth on a sapphire substrate or similar substrate, sometimes resulting in cracks at the delamination site and its surrounding area. Therefore, it is desirable to suppress the delamination between the α-Ga₂O₃ crystal film and the substrate.

[0005] This invention was made to solve such a problem, and its main purpose is to suppress the peeling between the α-Ga2O3 crystal film and the substrate. Technical solutions for solving the problem

[0006] To address the aforementioned issues, the inventors conducted in-depth research and conceived of a method that involves immersing an α-Cr₂O₃ substrate in an aqueous solution containing Ga ions at a temperature of 390°C or higher and a pressure of 22.1 MPa or higher in a supercritical state. Furthermore, it was discovered that in this method, even when an α-Ga₂O₃ crystal film is formed on the surface of the substrate to a thickness of 10 μm or more, delamination between the α-Ga₂O₃ crystal film and the substrate is difficult to occur. Moreover, it was found that the content of at least one alkali metal element in the α-Ga₂O₃ crystal film formed on the substrate is within a given range, thus completing the present invention.

[0007] That is, the composite substrate of the present invention comprises: a substrate; and an α-Ga₂O₃ crystal film disposed on the substrate, the film thickness being 10 μm or more, and the content of at least one alkali metal element being 1.2 × 10⁻⁶. 15 atoms / cm 3 Above and 1.0×10 18 atoms / cm 3 the following.

[0008] The method for manufacturing the composite substrate of the present invention is a method for manufacturing the above-mentioned composite substrate, wherein the substrate is immersed in an aqueous solution containing Ga ions in a supercritical state with a temperature of 390°C or higher and a pressure of 22.1 MPa or higher, thereby generating the α-Ga2O3 crystal film on the surface of the substrate.

[0009] In the method for manufacturing the gallium oxide crystal film of the present invention, the self-supporting α-Ga₂O₃ crystal film is obtained by removing the substrate from the composite substrate described above. Furthermore, the self-supporting α-Ga₂O₃ crystal film refers to a structure obtained by removing the substrate from the composite substrate; if the substrate is removed, it can also be transferred onto other substrates.

[0010] Alternatively, in the method for manufacturing the gallium oxide crystal film of the present invention, the self-supporting α-Ga2O3 crystal film is obtained by removing the substrate from the composite substrate manufactured using the above-described method for manufacturing the composite substrate. Invention Effects

[0011] In the composite substrate and its manufacturing method of the present invention, a composite substrate that suppresses delamination between the α-Ga₂O₃ crystal film and the substrate can be provided. The reason for this effect is presumably because, for example, at least one alkali metal element is included in the α-Ga₂O₃ crystal film at a suitable concentration. The manufacturing method of the composite substrate of the present invention is applicable to manufacturing composite substrates that suppress delamination between the α-Ga₂O₃ crystal film and the substrate. Furthermore, in the method for manufacturing the gallium oxide crystal film of the present invention, a self-supporting α-Ga₂O₃ crystal film is obtained by removing the substrate from the composite substrate with fewer cracks that suppress delamination between the α-Ga₂O₃ crystal film and the substrate, thus obtaining a gallium oxide crystal film with fewer cracks. Attached Figure Description

[0012] Figure 1 This is a cross-sectional view of the composite substrate 50. Figure 2 This is a longitudinal sectional view of the pressure vessel 10. Figure 3 This is a schematic diagram of the hydrothermal synthesis system 20. Figure 4 This is a surface SEM image of the composite substrate obtained in Example 1. Figure 5 This is a cross-sectional SEM image of the composite substrate obtained in Example 1. Figure 6 This is a schematic cross-sectional view showing the configuration of the AD device 120. Detailed Implementation

[0013] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Figure 1 This is a cross-sectional view of the composite substrate 50. Figure 2 This is a longitudinal sectional view of the pressure vessel 10. Figure 3 This is a schematic diagram of the hydrothermal synthesis system 20.

[0014] [Composite substrate] The composite substrate 50 is a plate-shaped component, comprising a base substrate 52 and an α-Ga₂O₃ crystal film 54 disposed on the base substrate 52. The area of ​​the composite substrate 50 is, for example, 1 mm². 2 The above is preferably 10mm. 2 above.

[0015] The substrate 52 serves as a seed substrate for the α-Ga₂O₃ crystal film 54. The substrate 52 is preferably a substrate with a corundum structure, and particularly preferably a substrate oriented along both the c-axis and an axis perpendicular to the c-axis (a-axis, m-axis, etc.) (a biaxially oriented substrate). The biaxially oriented substrate can be polycrystalline, a mosaic crystal (a collection of crystals with slightly offset crystal orientations), or a single crystal. The substrate 52 can be c-oriented with an offset angle of less than 10° in the substrate normal direction. The substrate 52 may also have other substrates on a surface opposite to the surface where the α-Ga₂O₃ crystal film 54 is formed (forming surface 52a).

[0016] The substrate 52 is an α-Cr₂O₃ substrate. The α-Cr₂O₃ substrate can be, for example, composed of α-Cr₂O₃ free of any components other than unavoidable impurities (referred to as a high-purity α-Cr₂O₃ substrate), or it can contain α-Cr₂O₃ and include metallic elements and / or half-metallic elements other than Cr, such as Ti, Fe, Al, Mg, Si, and Ca, within a total molar amount not exceeding that of Cr. These metallic elements and / or half-metallic elements can be dissolved in α-Cr₂O₃, or they can be dissolved in α-Cr₂O₃ as crystalline phases such as oxide crystals (e.g., α-Al₂O₃). Such solid solutions are also referred to as α-Cr₂O₃ solid solutions. High-purity α-Cr₂O₃ substrates and α-Cr₂O₃ solid solution substrates containing at least one of Fe and Ti are particularly suitable as α-Cr₂O₃ substrates.

[0017] An α-Ga₂O₃ crystal film 54 is formed on one side (formation surface 52a) of a substrate 52 with a thickness of 10 μm or more. The α-Ga₂O₃ crystal 55 constituting the α-Ga₂O₃ crystal film 54 is a crystal with a corundum structure. The α-Ga₂O₃ crystal film 54 is preferably oriented along two axes: the c-axis and an axis perpendicular to the c-axis (biaxial orientation). The α-Ga₂O₃ crystal film 54 can be polycrystalline, mosaic crystal, or single crystal. The α-Ga₂O₃ crystal film 54 can be c-oriented with an offset angle of less than 10° in the direction normal to the substrate. The α-Ga₂O₃ crystal film 54 contains at least one alkali metal element in an amount of 1.2 × 10⁻⁶. 15 ~1.0×10 18 atoms / cm 3 Examples of alkali metal elements include Li, Na, and K. The content of each of Li, Na, and K can be 1.2 × 10⁻⁶. 15 atoms / cm 3 Above and 1.0×10 18 atoms / cm 3The following are possible conditions: The crystal orientation difference between the α-Ga₂O₃ crystal film 54 and the substrate 52 on both the (0001) and (10-10) planes is 0.4° or less. The half-width of the X-ray rocking curve (XRC) of both the (006) and (104) planes of the α-Ga₂O₃ crystal film 54 is 2000 arcsec or less. The content of at least one of Cr and Ni in the α-Ga₂O₃ crystal film 54 is 2.0 × 10⁻⁶. 15 ~1.0×10 17 atoms / cm 3 It could be that the content of Li, Na, and K in the α-Ga₂O₃ crystal film 54 is 1.2 × 10⁻⁶ each. 15 ~1.0×10 18 atoms / cm 3 The α-Ga₂O₃ crystal film 54 may contain dopants. Examples of dopants include elements from Group 14 such as carbon (C), silicon (Si), germanium (Ge), tin (Sn), and lead (Pb). By including dopants in the α-Ga₂O₃ crystal film 54, the conductivity of the α-Ga₂O₃ crystal film 54 can be controlled.

[0018] [Fabrication method of composite substrate] Next, the method for manufacturing the composite substrate 50 will be described. In the method for manufacturing the composite substrate 50, the substrate 52 is immersed in an aqueous solution containing Ga ions, and the temperature is set to a supercritical state of 390°C or higher (preferably 400°C or higher) and pressure of 22.1 MPa or higher, thereby generating an α-Ga2O3 crystal film 54 on the surface of the substrate 52.

[0019] Examples of aqueous solutions containing Ga ions include gallium halide aqueous solutions, gallium nitrate aqueous solutions, gallium sulfate aqueous solutions, and gallium hydroxide aqueous solutions. Examples of gallium halides include gallium chloride, gallium bromide, and gallium iodide. Aqueous solutions containing Ga ions may contain alkali metal elements (alkali metal ions). Examples of alkali metal elements include Li, Na, and K. The pH of the aqueous solution containing Ga ions is preferably adjusted to 9.0–11.0 (more preferably 9.5–10.5) using a pH adjuster. As a pH adjuster, an aqueous solution of an alkali metal hydroxide (e.g., KOH aqueous solution) or an aqueous solution containing ammonium ions (e.g., ammonium water) can be used. The concentration of Ga ions in the aqueous solution is not particularly limited, but can be, for example, 0.1 M or more and 10 M or less.

[0020] Preferably, the substrate 52 immersed in the aqueous solution containing Ga ions has its modified layer removed on at least one surface (the surface forming surface 52a) by CMP (chemical mechanical polishing), annealing, etching, RIE (reactive ion etching), or the like. When the substrate 52 is immersed in the aqueous solution containing Ga ions, if the surface where the modified layer is removed is positioned in contact with the aqueous solution containing Ga ions, an α-Ga₂O₃ crystal film 54 is formed on the surface where the modified layer has been removed. When immersing the substrate 52 in the aqueous solution containing Ga ions, the substrate 52 can be placed or fixed to a Pt-made fixture or the like for immersion.

[0021] To establish the Ga-ion-containing aqueous solution in a supercritical state at a temperature of 390°C or higher and a pressure of 22.1 MPa or higher, it is preferable to place the Ga-ion-containing aqueous solution in a pressure-resistant container and set the temperature to 390°C or higher and the pressure to 22.1 MPa or higher. The pressure is determined based on the internal volume of the pressure-resistant container, the volume of the aqueous solution placed in the pressure-resistant container, the temperature inside the pressure-resistant container, and the setting of the pressure regulating valve. The reaction time is not particularly limited, but can be, for example, 0.5 hours or more and 100 hours or less. After the reaction is completed, the temperature inside the pressure-resistant container is lowered, and the substrate 52 (composite substrate 50) with the α-Ga₂O₃ crystal film 54 attached is removed from the pressure-resistant container.

[0022] To generate a doped α-Ga₂O₃ crystal film 54, it is only necessary to contain ions corresponding to the dopant in the aqueous solution containing Ga ions. Examples of dopants include elements from Group 14 such as carbon (C), silicon (Si), germanium (Ge), tin (Sn), and lead (Pb). By containing a dopant in the α-Ga₂O₃ crystal film 54, the conductivity of the α-Ga₂O₃ crystal film 54 can be controlled.

[0023] Figure 2 An example of a pressure vessel is shown. Figure 2 The pressure-resistant container 10 is made of stainless steel, and a lid 12 with a male threaded protrusion 12a is screwed into the female thread of the opening of the bottomed cylindrical container body 11. The internal volume of the pressure-resistant container 10 is preferably 50 mL or more. An aqueous solution 14 containing Ga ions is placed in the container body 11 of the pressure-resistant container 10. The aqueous solution 14 is preferably adjusted to pH 9.0 to 11.0 (more preferably to pH 9.5 to 10.5). A substrate 52 disposed on the bottom surface of a box-shaped clamp 16 made of Pt is immersed in the aqueous solution 14. The substrate 52 is disposed with the surface from which the modified layer has been removed facing upwards.

[0024] Figure 3This is a schematic diagram of the hydrothermal synthesis system 20. In this system, a pressure vessel 10 is installed in the electric furnace shell 22. A heater 24 and a thermocouple 26 for measuring the furnace temperature are installed inside the furnace shell 22. A thermocouple 28 for measuring the internal temperature of the pressure vessel 10 is installed in the pressure vessel 10. The power supplied to the heater 24 is controlled so that the furnace temperature measured by the thermocouple 26 becomes the set temperature. A pipe 30 is connected to the pressure vessel 10. One end 30a of the pipe 30 is located inside the pressure vessel 10, and the other end 30b is exposed to the atmosphere. The pipe 30 is cooled by cooling water in a cooling water tank 40. A pressure gauge 32, a safety valve 34, and a pressure regulating valve 36 are installed in the pipe 30 between the cooling water tank 40 and the other end 30b. The pressure vessel 10 is heated by heater 24 to a temperature of 390°C or higher and an internal pressure of 22.1 MPa or higher. The internal pressure of the pressure vessel 10 is determined by its internal volume, the volume of the aqueous solution 14 placed in it, the internal temperature, and the setting of the pressure regulating valve 36. Therefore, to achieve an internal pressure of 22.1 MPa or higher while maintaining an internal temperature of 390°C or higher, the volume of the aqueous solution 14 placed in the pressure vessel 10 can be adjusted. After maintaining this state for a given time, the internal temperature of the pressure vessel 10 is cooled to room temperature. The substrate 52 (composite substrate 50) with the α-Ga₂O₃ crystal film 54 attached is then removed from the pressure vessel 10, washed with pure water, and dried using a desiccator.

[0025] [Preparation of gallium oxide crystal films] Next, the method for fabricating a gallium oxide crystal film will be described. One example of the method for fabricating a gallium oxide crystal film is obtaining a self-supporting α-Ga₂O₃ crystal film 54 by removing the substrate 52 from the composite substrate 50. Methods for removing the substrate 52 from the composite substrate 50 include grinding, polishing, laser lift-off, etching of the substrate portion using acid or alkali, and RIE (reactive ion etching). By removing the substrate 52 from the composite substrate 50, a self-supporting α-Ga₂O₃ crystal film 54 can be obtained. The α-Ga₂O₃ crystal film 54 can also be transferred onto other substrates after removing the substrate 52.

[0026] In the composite substrate 50 and the method for manufacturing the composite substrate 50 described above, a composite substrate that suppresses delamination between the α-Ga₂O₃ crystal film 54 and the substrate 52 can be provided. The reason for this effect is presumably because, for example, at least one alkali metal element is included in the α-Ga₂O₃ crystal film 54 at a suitable concentration. Furthermore, by including at least one alkali metal element in the α-Ga₂O₃ crystal film 54 at a suitable concentration, it is also expected to suppress heterogeneous phases such as β-Ga₂O₃ and stably generate α-Ga₂O₃ crystals. The method for manufacturing the composite substrate 50 is suitable for manufacturing the composite substrate 50. In the method for manufacturing the gallium oxide crystal film, the substrate 52 is removed from the composite substrate 50, which has few cracks and suppresses delamination between the α-Ga₂O₃ crystal film 54 and the substrate 52, thus obtaining a self-supporting α-Ga₂O₃ crystal film 54 with few cracks. Furthermore, in the composite substrate 50, the ratio of the peeled area of ​​the α-Ga2O3 crystal film 54 to the substrate 52 can be, for example, 10% or less of the forming surface 52a, preferably 3% or less.

[0027] Furthermore, in the composite substrate 50, the thickness of the α-Ga₂O₃ crystal film 54 is 10 μm or more. Therefore, by simply removing the substrate 52, a self-supporting α-Ga₂O₃ crystal film 54 with a thickness of 10 μm or more can be obtained. Such an α-Ga₂O₃ crystal film 54 is suitable for use in power semiconductors with vertical structures where current needs to flow in the thickness direction. Additionally, the thickness of the α-Ga₂O₃ crystal film 54 can be adjusted appropriately according to the application, and can be, for example, less than 100 μm. The thickness of the α-Ga₂O₃ crystal film 54 can be adjusted, for example, by changing the amount and concentration of Ga used, and the hydrothermal synthesis time.

[0028] Furthermore, in the composite substrate 50, the base substrate 52 is an α-Ga2O3 substrate. Therefore, by generating an α-Ga2O3 crystal film in a suitable state, the peeling between the α-Ga2O3 crystal film 54 and the base substrate 52 is further suppressed.

[0029] Furthermore, in the composite substrate 50, it is preferable that the crystal orientation difference between the (0001) plane and the (10-10) plane of the α-Ga2O3 crystal film 54 and the substrate 52 is 0.4° or less; in other words, the substrate 52 and the crystal orientation are substantially the same. If the crystal orientation is substantially the same, strain is less likely to occur between the α-Ga2O3 crystal film 54 and the substrate 52, thus further suppressing delamination between the two. In addition, the crystal orientation difference between the (0001) plane and the (10-10) plane is more preferably 0.3° or less, more preferably 0.2° or less, and even more preferably 0.1° or less.

[0030] Furthermore, when using α-Ga2O3 crystals in power semiconductors requiring high voltage withstand capability, the insulation breakdown electric field characteristics are influenced by crystal quality, thus requiring high crystal quality. Therefore, in the composite substrate 50, it is preferable that the half-width of the X-ray rocking curves of both the (006) and (104) planes of the α-Ga2O3 crystal film 54 is 2000 arcsec or less, in other words, the crystallinity (crystal quality) is very high. In addition, the half-width of the X-ray rocking curve of the (006) plane is preferably 1600 arcsec or less, but can also be 1000 arcsec or less, or even 100 arcsec or less. The half-width of the X-ray rocking curve of the (104) plane is preferably 1900 arcsec or less, but can also be 1000 arcsec or less, or even 400 arcsec or less. The half-widths of the X-ray rocking curves of both the (006) and (104) planes can each be 50 arcsec or more.

[0031] Furthermore, in the composite substrate 50, the content of at least one of Cr and Ni in the α-Ga₂O₃ crystal film 54 is preferably 2.0 × 10⁻⁶. 15 ~1.0×10 17 atoms / cm 3 This further suppresses the peeling between the α-Ga₂O₃ crystal film 54 and the substrate 52. Furthermore, the content of Cr and Ni is preferably 2.0 × 10⁻⁶. 15 ~1.0×10 17 atoms / cm 3 Furthermore, the total content of Cr and Ni is preferably 1.6 × 10⁻⁶. 17 atoms / cm 3 The preferred value is 5.0×10. 16 atoms / cm 3 the following.

[0032] Furthermore, in the composite substrate 50, the content of Li, Na, and K in the α-Ga₂O₃ crystal film 54 is preferably 1.2 × 10⁻⁶. 15 ~1.0×10 18 atoms / cm 3 Furthermore, the sum of the contents of Li, Na, and K is preferably 1.2 × 10⁻⁶. 15 ~1.2×10 18 atoms / cm 3 .

[0033] Furthermore, the present invention is not limited to the above-described embodiments, and can of course be implemented in various ways within the technical scope of the present invention.

[0034] For example, in the above embodiment, the substrate 52 is an α-Cr2O3 substrate, but the substrate 52 can also be a sapphire substrate, an α-Fe2O3 substrate, an α-Ga2O3 substrate, etc. However, depending on the type of substrate 52, sometimes the α-Ga2O3 crystals are not formed as a film but as granules, or they easily form heterogeneous phases such as β-Ga2O3 crystals. As long as the substrate 52 is an α-Cr2O3 substrate, the α-Ga2O3 crystals are easily formed as a film and it is difficult for heterogeneous phases to occur, so it is preferred. In particular, as long as the substrate 52 is an α-Cr2O3 solid solution substrate, the α-Ga2O3 crystal film 54 has higher crystallinity, and the crystal orientation difference between the α-Ga2O3 crystal film 54 and the substrate 52 is smaller, so it is preferred. Example

[0035] The following describes embodiments of the present invention. Furthermore, the following embodiments do not limit the scope of the present invention in any way.

[0036] [Example 1] 1. Substrate preparation A commercially available α-Cr2O3 single crystal substrate with c-side (no offset angle) used as a high-purity α-Cr2O3 substrate is cut into square sections of approximately 4 mm (□4 mm). Both sides are mirror-polished using diamond slurry, and then CMP (Continuous Metallurgy Processing) is applied to one side for further finishing. In the CMP process, the finished side is referred to as the substrate CMP side, and the other side is referred to as the substrate non-CMP side.

[0037] 2. Hydrothermal synthesis A 0.1M aqueous solution of gallium nitrate octahydrate (prepared by KISHIDA Chemicals) was prepared as a pH adjuster, and the pH was adjusted to 10.0 using a 1M KOH aqueous solution to obtain the raw material solution. Next, a 4mm square c-plane α-Cr₂O₃ single crystal substrate (substrate 52) was placed with its CMP surface facing upwards within a clamp 16 made of 50μm thick Pt foil with a height of 10mm, width of 10mm, and depth of 10mm. Figure 2A pressure vessel 10 (19 mm inner diameter, 50 mL internal volume) made of SUS316 steel was further filled with 45 mL of the aforementioned raw material solution and sealed. Next, the pressure vessel 10 was installed in the electric furnace housing 22 of the hydrothermal synthesis system 20. The pressure regulating valve 36 was pre-installed with the internal pressure of the pressure vessel 10 set to 30.0 MPa. Then, the entire pressure vessel 10 was heated using the heater 24 of the electric furnace housing 22, setting the internal temperature of the pressure vessel 10 to 410°C. At this time, the internal pressure of the pressure vessel 10 was 30.0 MPa. This condition was maintained for 24 hours. After the internal temperature of the pressure vessel 10 was cooled to room temperature, the resulting substrate (composite substrate) was removed from the pressure vessel 10, washed with pure water, and dried using a desiccator. A crystalline film was formed on the CMP substrate surface of this composite substrate.

[0038] 3. Removal of the substrate The substrate side (non-CMP side) of the composite substrate obtained in step 2 above is adhered to a polishing plate using wax. The surface of the crystal film is polished using diamond paste, and then smoothly finished using CMP (CMP side of the crystal film). The composite substrate is removed from the polishing plate, and a sapphire substrate is bonded to the CMP side of the crystal film on the composite substrate using wax to obtain a bond. Furthermore, the sapphire side of the bond is adhered to the polishing plate using wax, and the substrate (Cr2O3 portion) is removed by grinding using a polishing apparatus with #1000 and #6000 grinding stones. Thus, a gallium oxide crystal film transferred to a sapphire substrate is obtained. Since the sapphire substrate is adhered to the gallium oxide crystal film using wax, it can be easily removed. Thus, a self-supporting gallium oxide crystal film is obtained.

[0039] 4. Evaluation (1) Crystal phase For the crystal formed on the CMP substrate in section 2 above, XRD patterns were obtained using an XRD apparatus (Rigaku, RINT-TTRIII) under the following conditions. The results indicate that the main phase of the formed crystal film is α-Ga₂O₃. X-ray tube Cu target · Tube voltage 50kV · Tube current 300mA ·2θ / θ method ·2θ range 10°~80°

[0040] (2) Whether or not peeling occurs Regarding the composite substrate obtained in section 2 above, when visually confirming whether there is any peeling between the substrate and the α-Ga2O3 crystal film, although slight (less than 3%) peeling can be seen on the outer periphery of the composite substrate, it is not considered as overall peeling.

[0041] (3) Microstructure observation The results of observing the surface (α-Ga₂O₃ crystal film surface) of the composite substrate obtained in step 2 above using a scanning electron microscope (SEM, JSM-IT500, Nippon Electron) confirmed that... Figure 4 Such a crystalline film. After resin embedding of the substrate, a cross-section was prepared using a micro-tool, and a cross-section observation sample was prepared using a cross-section polishing instrument (Nippon Electron IB-19500CP). The reflected electron image of the obtained cross-section was photographed using a scanning electron microscope (Hitachi High-Technologies SU-5000). At this time, as... Figure 5 As shown, the α-Cr₂O₃ (substrate) and α-Ga₂O₃ crystal films of the composite substrate can be easily distinguished using contrast difference. The film thickness of the α-Ga₂O₃ crystal film was measured based on this cross-sectional SEM image. The results are shown in Table 1. Figure 4 , 5 It can be seen that almost no micropores were identified in the crystal film formed on the substrate.

[0042] (4) Half-width of X-ray rocking curve XRC measurements of the (006) and (104) planes of the crystal formed on the CMP substrate in section 2 above were performed using an XRD apparatus (Bruker-AXS, D8-DISCOVER). Specifically, measurements were performed on 2θ, ω, χ, and... After adjusting the method to reveal the peaks of the (006) or (104) planes of α-Ga₂O₃, the XRC curves were vertically oriented. The conditions were: ω = 20.0–20.4° for (006) plane measurements with a tube voltage of 40 kV, tube current of 40 mA, and an anti-scattering slit of 3 mm; ω = 16.5–17.5° for (104) plane measurements; ω step size of 0.001°; and counting time of 0.5 seconds. Furthermore, the X-ray source was obtained by parallel monochromaticizing CuK α-rays with a Ge(0₂₂) asymmetric reflector monochromator. The half-width of the obtained α-Ga₂O₃ XRC curves was determined using XRD analysis software (Bruker-AXS). The curve was smoothed using "LEPTOS" Ver4.03, and then a peak search was performed to determine the peak. The results are shown in Table 1.

[0043] (5) EBSD (backscattered electron diffraction) Using the sample prepared for cross-sectional observation as described above (3), EBSD measurements were performed using a scanning electron microscope (Hitachi High-Technologies SU-5000) equipped with an EBSD (Oxford Instruments Corporation, Nordlys Nano). According to the obtained inverse pole diagram orientation mapping, the α-Ga2O3 crystal film is an orientation layer with c-axis orientation in the substrate normal direction, and also a biaxial orientation layer with orientation in the in-plane direction of the substrate. In the further obtained crystal orientation mapping, the tilt angle distributions of α-Ga2O3 and α-Cr2O3 relative to the (0001) and (10-10) orientations were analyzed, and the difference in the peak positions of the obtained angle distributions was calculated. Specifically, firstly, for the crystal orientation mapping image measured in the field of view including both the α-Ga2O3 film and the α-Cr2O3 substrate, in the histogram of the tilt angle distribution represented by the Legend of the analysis program, with the class width of the histogram set to 0.010, the peak position of the tilt angle distribution at the (0001) orientation of the α-Ga2O3 film portion is within the range of 10 to 11 degrees, and the peak position of the tilt angle distribution at the (10-10) orientation of the α-Ga2O3 film portion is within the range of 10 to 11 degrees, and the axis alignment is performed using the virtual chamber of the analysis program. The angle of the peak position of the tilt angle distribution at the (0001) orientation of the α-Ga2O3 film portion at this time is set as c1[°] (10 < c1 < 11), and the angle of the peak position of the tilt angle distribution at the (10-10) orientation of the α-Ga2O3 portion is set as a1[°] (10 < a1 < 11). Next, while maintaining axial alignment, the angle c2 [°] of the peak position of the tilt angle distribution in the (0001) orientation of the substrate (α-Cr2O3) portion was determined, and the (0001) orientation difference between the substrate and the α-Ga2O3 film was calculated using |c1-c2| [°]. Similarly, the angle a2 [°] of the peak position of the tilt angle distribution in the (10-10) orientation of the substrate (α-Cr2O3) portion was determined, and the (10-10) orientation difference between the substrate and the α-Ga2O3 film was calculated using |a1-a2| [°]. The results are shown in Table 1. According to these results, in Example 1, the orientation difference between the substrate and the α-Ga2O3 film is 0.10 degrees in the (0001) orientation and 0.13 degrees in the (10-10) orientation, resulting in an α-Ga2O3 film with approximately the same crystal orientation as the substrate. Furthermore, in the above description, the crystal orientation

[0001] of the (0001) plane is defined as the (0001) orientation, and the crystal orientation [10-10] of the (10-10) plane is defined as the (10-10) orientation. The conditions for EBSD measurement are as follows. <EBSD Measurement Conditions> Accelerating voltage: 15kV • Highlight intensity: 70 • Working distance: 22.5mm • Step size: 0.4μm • Sample tilt angle: 70° • Measurement procedure: Aztec • Parser: OXFORD HKL CHANNEL 5

[0044] (6) Composition Analysis Compositional analysis (D-SIMS analysis) of the α-Ga2O3 crystal film on the surface of the composite substrate obtained in step 2 above was performed using a secondary ion mass spectrometry (SIMS) apparatus. The conditions for this D-SIMS analysis are as follows. <D-SIMS Analysis Conditions> • Device: CAMECA IMS-7f Primary ionic species: O2 + • Primary ion acceleration voltage: 8.0kV The content of each ion was converted to "atoms / cm" using a Ga2O3 standard sample. 3 The concentration distribution along the depth direction was generated using the unit "", and the average value was calculated as the average value from the surface to a depth of 1 μm to 2 μm. The results are shown in Table 1.

[0045] [Example 2] When preparing the raw material solution, a 1M LiOH aqueous solution was used as a pH adjuster to adjust the pH of the 0.1M gallium nitrate octahydrate aqueous solution to 10.5. The internal temperature of the pressure vessel 10 was set to 400°C. Otherwise, the sample was prepared and evaluated using the same method as in Example 1. The main phase of the crystalline film formed on the substrate was α-Ga₂O₃. The various evaluation results are shown in Table 1.

[0046] [Example 3] When preparing the raw material solution, a 1M NaOH aqueous solution was used as a pH adjuster to adjust the pH of a 0.1M aqueous solution of gallium nitrate octahydrate to 9.5. Otherwise, samples were prepared and evaluated using the same method as in Example 1. The main phase of the crystalline film formed on the substrate was α-Ga₂O₃. Various evaluation results are shown in Table 1.

[0047] [Example 4] A substrate for an α-Cr₂O₃ solid solution was fabricated as follows. As raw material powders, 100 parts by weight of Cr₂O₃ powder were mixed with 5 parts by weight of TiO₂ powder and 16 parts by weight of Fe₂O₃ powder. The resulting wet-mixed powder was then... Figure 6 The AD (aerosol deposition) device 120 shown forms an AD film on a sapphire substrate (50.8 mm (2 inches) in diameter, 1.0 mm in thickness, c-plane, offset angle 0.5°). Figure 6 The AD apparatus 120 shown is configured for use in the AD process, which involves spraying raw material powder onto a substrate in an atmosphere with a pressure lower than atmospheric pressure. This film-forming apparatus 120 includes: an aerosol generation unit 122 for generating an aerosol containing raw material powder; and a film-forming unit 130 for spraying the raw material powder onto a sapphire substrate 121 to form a film containing the raw material powder. The aerosol generation unit 122 includes: an aerosol generation chamber 123 for containing the raw material powder and receiving a carrier gas from a gas cylinder (not shown) to generate the aerosol; a raw material supply pipe 124 for supplying the generated aerosol to the film-forming unit 130; and a vibrator 125 for applying vibration to the aerosol generation chamber 123 and the aerosol therein at a vibration frequency of 10–100 Hz. The film-forming unit 130 includes: a film-forming chamber 132 for spraying aerosol onto a sapphire substrate 121; a substrate holder 134 disposed inside the film-forming chamber 132 and fixing the sapphire substrate 121; and an X-Y stage 133 for moving the substrate holder 134 in the X-Y axis direction. Furthermore, the film-forming unit 130 includes: a spray nozzle 136 with a slit 137 formed at its front end for spraying aerosol onto the sapphire substrate 121; and a vacuum pump 138 for depressurizing the film-forming chamber 132.

[0048] The AD film formation conditions are as follows: The carrier gas is Ar, and a ceramic nozzle with a slit formed on a long side of 5 mm × a short side of 0.3 mm is used. The nozzle scanning conditions are as follows: at a scanning speed of 0.5 mm / s, the nozzle repeatedly moves 55 mm forward in a direction perpendicular to the long side of the slit, then 5 mm in the direction of the long side of the slit, then 55 mm in a direction perpendicular to the long side of the slit and returning, and then 5 mm in the direction of the long side of the slit and opposite to the initial position. At the point where the nozzle has moved 55 mm from the initial position in the direction of the long side of the slit, it scans in the opposite direction, returning to the initial position. This cycle is considered one cycle, and the process is repeated 400 times. In one cycle of film formation at room temperature, the set pressure of the carrier gas is adjusted to 0.07 MPa, the flow rate is adjusted to 9 L / min, and the chamber pressure is adjusted to below 100 Pa. The thickness of the AD film formed in this way is approximately 100 μm.

[0049] The sapphire substrate with the AD film formed was removed from the AD device and annealed at 1680°C for 4 hours in a nitrogen atmosphere. The resulting substrate was then fixed to a ceramic platform, and the side with the AD film formed was ground to #2000 using a grinding stone to achieve a flat surface. Next, the surface was smoothed using diamond abrasive. The abrasive grain size was reduced in stages from 3 μm to 0.5 μm, improving flatness. After being cut to a size of □4 mm using a dicing machine, a mirror finish was achieved using chemical mechanical polishing (CMP) with colloidal silica to obtain the composite substrate. The arithmetic mean roughness Ra after processing was 0.1 nm, the grinding and abrasion amount was 50 μm, and the thickness of the composite substrate after polishing was 1.05 mm. The side with the AD film formed is referred to as the "surface".

[0050] Compositional analysis of the composite substrate surface was performed using an electron probe microanalyzer (FE-EPMA) (JEOL Ltd., JXA-8500F) with a probe size of 30 μm × 30 μm. FE-EPMA measurements were conducted under conditions of an accelerating voltage of 15 kV and an irradiation current of 50 nA. The results showed the detection of Cr, O, Ti, and Fe. The quantitative values ​​(atomic percentages of atoms other than O) for the detected elements were: Cr 83.7 at%, Ti 3.7 at%, and Fe 12.6 at%.

[0051] The composite substrate prepared as described above was used with the AD film (α-Cr2O3 solid solution substrate) side facing upwards. Otherwise, samples were prepared and evaluated using the same method as in Example 1. The main phase of the crystalline film formed on the substrate was α-Ga2O3. Various evaluation results are shown in Table 1.

[0052] Table 1

[0053] [Comparative Example 1] A 4mm c-plane sapphire substrate (without offset angle and surface CMP treatment completed) was used as the substrate. An α-Ga₂O₃ crystal film was fabricated using atomized CVD as follows: An aqueous solution of 36% hydrochloric acid with a gallium acetylacetonate concentration of 0.08 mol / L and a volume percentage of 1.5% was used as the feed solution. This feed solution was atomized by vibrating at 2.4 MHz using an ultrasonic transducer and introduced into the film deposition chamber via nitrogen gas. In the film deposition chamber, a substrate was pre-positioned on a pedestal, and the chamber was heated to 490°C. The atomized feed solution was deposited into a film through a CVD reaction at the surface of the substrate. This film deposition process was repeated 5 times for 60 minutes to deposit a crystal film onto the substrate. The main phase of the crystal film formed on the substrate was identified as α-Ga₂O₃ by XRD. In Comparative Example 1, more than 50% of the film was peeled off visually, and numerous cracks appeared around the peeled portion. Therefore, the film thickness was measured by observing the cross-section of the portion where partial peeling had not occurred. The various evaluation results are shown in Table 2.

[0054] [Comparative Example 2] Using the same α-Cr₂O₃ substrate as in Example 1, an α-Ga₂O₃ crystalline film was fabricated via atomization CVD, similar to Comparative Example 1. However, the film formation process was repeated 10 times for 60 minutes each, for a total of 600 minutes. The main phase of the crystalline film formed on the substrate was confirmed as α-Ga₂O₃ by XRD. In Comparative Example 2, more than 40% of the film was visually peeled off, with numerous cracks appearing around the peeled areas. The film thickness was measured by cross-sectional observation of the areas where partial peeling did not occur. Various evaluation results are shown in Table 2.

[0055] Table 2

[0056] As shown in Table 2, the content of each alkali metal element in the α-Ga₂O₃ crystal film is less than 1.2 × 10⁻⁶. 15 atoms / cm 3 In Comparative Examples 1 and 2, peeling occurred over a wide area between the α-Ga₂O₃ crystal film and the substrate. On the other hand, as shown in Table 1, the content of at least one alkali metal element was 1.2 × 10⁻⁶. 15 ~1.0×10 18 atoms / cm 3In Examples 1 to 4, the peeling between the α-Ga2O3 crystal film and the substrate was suppressed, and the peeling area was less than 3% in each example. Furthermore, in Examples 1 to 4, the crystal orientation difference between the α-Ga2O3 crystal film and the (0001) and (10-10) planes of the substrate was less than 0.4°, and the half-width of the X-ray rocking curves of the (006) and (104) planes of the α-Ga2O3 crystal film was less than 2000 arcsec.

[0057] In addition, the “~” used in this specification to indicate a range of values ​​is used to mean that the values ​​described before and after it are included as the lower and upper limits.

[0058] This application takes Japanese Patent Application No. 2021-075004, filed on April 27, 2021, as the basis for its priority claim, the entire contents of which are incorporated herein by reference. Industrial applicability

[0059] This invention can be applied to, for example, materials for power semiconductors. Explanation of reference numerals in the attached figures

[0060] 10 Pressure vessel, 11 Vessel body, 12 Lid, 12a Protrusion, 14 Aqueous solution containing Ga ions, 16 Clamp, 20 Hydrothermal synthesis system, 22 Electric furnace shell, 24 Heater, 26 Thermocouple for furnace temperature measurement, 28 Thermocouple for pressure vessel, 30 Piping, 30a One end, 30b The other end, 32 Pressure gauge, 34 Safety valve, 36 Pressure regulating valve, 40 Cooling water tank, 50 Composite substrate, 52 Substrate, 52a Forming surface, 54 α-Ga2O3 crystal film, 55 α-Ga2O3 crystal, 120 AD device, 121 Sapphire substrate, 122 Aerosol generation section, 123 Aerosol generation chamber, 124 Raw material supply pipe, 125 Vibrator, 130 Film forming section, 132 Film forming chamber, 133 X-Y stage, 134 Substrate holder, 136 Nozzle, 137 Slit, 138 Vacuum pump.

Claims

1. A composite substrate comprising: Substrate; and An α-Ga₂O₃ crystal film, disposed on the substrate, has a thickness of 10 μm or more, and contains at least one alkali metal element in an amount of 1.2 × 10⁻⁶. 15 atoms / cm 3 Above and 1.0×10 18 atoms / cm 3 the following, The substrate is an α-Cr2O3 substrate.

2. The composite substrate according to claim 1, wherein, The crystal orientation difference between the α-Ga2O3 crystal film and the (0001) and (10-10) planes of the substrate is less than 0.4°.

3. The composite substrate according to claim 1 or 2, wherein, The half-width of the X-ray rocking curves of the (006) and (104) planes of the α-Ga2O3 crystal film is less than 2000 arcsec.

4. The composite substrate according to claim 1 or 2, wherein, The α-Ga₂O₃ crystal film contains at least one of Cr and Ni in an amount of 2.0 × 10⁻⁶. 15 atoms / cm 3 Above and 1.0×10 17 atoms / cm 3 the following.

5. The composite substrate according to claim 1 or 2, wherein, The α-Ga₂O₃ crystal film contains 1.2 × 10⁻⁶ Li, Na, and K respectively. 15 atoms / cm 3 Above and 1.0×10 18 atoms / cm 3 the following.

6. A method for manufacturing a composite substrate, comprising manufacturing the composite substrate according to any one of claims 1 to 5, wherein, By immersing a substrate in an aqueous solution containing Ga ions, and setting the temperature to above 390°C and the pressure to above 22.1 MPa in a supercritical state, the α-Ga₂O₃ crystal film is formed on the surface of the substrate. The aqueous solution contains alkali metal elements.

7. A method for preparing a gallium oxide crystal film, wherein the self-supporting α-Ga2O3 crystal film is obtained by removing the substrate from the composite substrate according to any one of claims 1 to 5.

8. A method for preparing a gallium oxide crystal film, wherein the self-supporting α-Ga2O3 crystal film is obtained by removing the substrate from a composite substrate manufactured using the method for preparing a composite substrate according to claim 6.

Citation Information

Patent Citations

  • Semiconductor device

    JP2014072533A

  • Semiconductor device

    JP2016025256A

  • Printer

    JP2021075004A

  • Ga2o3 semiconductor element

    CN103765593A

  • Production method for oxide crystal thin film

    CN104736747A